The roles of species’ relatedness and climate of origin in determining optical leaf traits over a large set of taxa growing at high elevation and high latitude - Hartikainen, Saara M.; Robson, T. Matthew (Frontiers in Plant Science, 2022)
Climate change is driving many mountain plant species to higher elevations and northern plant species to higher latitudes. However, various biotic or abiotic constraints may restrict any range shift, and one relevant factor for migration to higher elevations could be species' ability to tolerate high UV-doses. Flavonoids are engaged in photoprotection, but also serve multiple ecological roles. We compared plant optical leaf trait responses of a large set of taxa growing in two botanical gardens (French Alps and southern Finland), considering potential constraints imposed by the relatedness of taxa and the legacy of climatic conditions at plants' original collection sites. The segregation of optically measured leaf traits along the phylogeny was studied using a published mega-tree GBOTB.extended.tre for vascular plants as a backbone. For a subset of taxa, we investigated the relationship between climatic conditions (namely solar radiation, temperature and precipitation at a coarse scale) at the plants’ original collection site and current trait values. Upon testing the phylogenetic signal (Pagel's λ), we found a significant difference but intermediate lambda values overall for flavonol or flavone index (Iflav) and anthocyanin index (Iant), indicating that phylogenetic relatedness alone failed to explain the changes in trait values under a Brownian motion model of trait evolution. The local analysis (local indicator of phylogenetic association) indicated mostly positive autocorrelations for Iflav i.e. similarities in optically measured leaf traits, often among species from the same genus. We found significant relationships between climatic variables and leaf chlorophyll index (Ichl), but not Iflav, particularly for annual solar radiation. Changes in plants' Iflav across microhabitats differing in UV irradiance and predominately high Fv/Fm indicated that most plants studied had sufficient flexibility in photoprotection, conferred by Iflav, to acclimate to contemporary UV irradiances in their environment. While not explaining the mechanisms behind observed trait values, our findings do suggest that some high-elevation taxa display similar leaf flavonoid accumulation responses. These may be phylogenetically constrained and hence moderate plants’ capacity to adjust to new combinations of environmental conditions resulting from climate change.